Evaluación de tres membranas de colágeno cargadas con ácido gálico al 95 %: estudio in vitro (2022)
This research work focuses on the in vitro analysis of the relationship between biomaterials and components of natural origin, as a possible adjuvant treatment for periodontitis. It is known that the chronic inflammation of the gingival tissue is caused by an immune hyperresponse caused by the accumulation of dental biofilm on the root surface, triggering the progressive destruction of the periodontal tissues, compromising the support and stability of the teeth. Over time, different treatment alternatives have been proposed as adjuvants to scaling and root planing, such as: antibiotics, analgesics, probiotics, alternative therapies, among others.